Conundrums in practical theology - Miller-McLemore, Bonnie J.; Mercer, Joyce. (Theology in Practice, 2016)
In this landmark volume, internationally recognized scholars address key intellectual and practical conundrums that not only trouble practical theology but also reflect biases and breakdowns in the construction of theological knowledge in academy and religious communities at large. With critical facility and unheralded honesty that includes reflexivity about their own lives in the academy, the authors tackle complex issues that refuse easy solutions- racism, hierarchy of theory over practice, devaluation of small case studies, risks of interdisciplinarity to scholarly identity, inequities between Christian traditions, unreflective Christian-centrism, and tensions between the production of scholarship and public service. Outcomes of these issues will have serious implications for the discipline and the study of theology for years to come. Contributors include Tom Beaudoin, Eileen R. Campbell-Reed, Faustino M. Cruz, Jaco Dreyer, Courtney T. Goto, Tone Stangeland Kaufman, Joyce Ann Mercer, Bonnie J. Miller-McLemore, Phillis Isabella Sheppard, Katherine Turpin, Claire E. Wolfteich.